Sustainable Strategic Management: Integration of Environmental Principles in Business Management - Suharto Suharto (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2023)
Climate change, environmental degradation and sustainability demands are increasingly pressing companies to adopt environmentally friendly business practices. This research aims to explore and analyze the implementation of sustainable strategic management with a focus on the integration of environmental principles in business management. This research uses a qualitative approach with descriptive methods. The research results show that the integration of environmental principles in business management can make a significant contribution to corporate sustainability. By involving sustainable practices in all operational aspects, companies are able to reduce negative impacts on the environment, increase resource efficiency, and respond to increasing consumer demands regarding sustainability. In addition, employee involvement in sustainability initiatives and regular performance monitoring are also key factors in achieving holistic sustainability. Thus, the results of this research confirm that the application of environmental principles can provide long-term benefits, both for the company itself and for society and the environment at large.